Effects of plastics on reactor performance and microbial communities during acidogenic fermentation of food waste for production of volatile fatty acids. (October 2021) - Zhang, Le; Tsui, To-Hung; Loh, Kai-Chee; Dai, Yanjun; Tong, Yen Wah
Graphical abstract: Highlights: Acidogenic fermentation of plastic-containing FW for producing volatile fatty acids. Addition of HDPE and PS increased total VFA yields by 28% and 47%, respectively. Plastic degradation in acidogenic fermenters was confirmed, but with limited degree. Genus Defluviitoga and Phyla Thermotogae and Firmicutes dominated all the reactors. Potential HDPE-, PS- and PET-degrading microbes were speculated for further studies. Abstract: The aim of this work was to study the effects of plastics (high-density polyethylene (HDPE), polystyrene (PS), polypropylene (PP), and polyethylene terephthalate (PET)) on reactor performance and microbial communities during acidogenic fermentation of food waste for the production of volatile fatty acids (VFA). The addition of HDPE and PS increased total VFA yields by 28% and 47%, respectively, whereas the addition of PP and PET decreased total VFA yields by 6% and 2%, respectively. The highest enhancing performance of PS could be ascribed to its highly porous structure that could provide immobilization effects for microbial growth. Degradation of various plastics was confirmed by FESEM results, but the degrees were limited (i.e., 3.9–8.7%). Bacterial analysis showed that the addition of various plastics altered the community diversity. Phylum Thermotogae and genus Defluviitoga dominated all the reactors. Potential HDPE- and PS-degrading microbes could belong to genus Clostridium_sensu_stricto_8, while Tepidanaerobacter_syntrophicus could be PET-degrading microbes.